How Photoisomerization Drives Peptide Folding and Unfolding: Insights from QM/MM and MM Dynamics Simulations. (6th January 2016) - Xia, Shu‐Hua; Cui, Ganglong; Fang, Wei‐Hai; Thiel, Walter
Abstract: Photoswitchable azobenzene cross‐linkers can control the folding and unfolding of peptides by photoisomerization and can thus regulate peptide affinities and enzyme activities. Using quantum mechanics/molecular mechanics (QM/MM) methods and classical MM force fields, we report the first molecular dynamics simulations of the photoinduced folding and unfolding processes in the azobenzene cross‐linked FK‐11 peptide. We find that the interactions between the peptide and the azobenzene cross‐linker are crucial for controlling the evolution of the secondary structure of the peptide and responsible for accelerating the folding and unfolding events. They also modify the photoisomerization mechanism of the azobenzene cross‐linker compared with the situation in vacuo or in solution.